The effects of cash flows and accruals on the share price in Jordan with special reference to financial crisis: audit quality as a moderator - Oroud, Yazan Salameh Mottee author (School of Business Innovation & Technopreneurship, 2018)
The scope of the present study is effects of cash flows and accruals on the share prices of Jordanian companies listed on ASE during the period 2002-2104, as well as the potential role of audit quality in moderating these effects. Therefore, the subject boundaries of this study are cash flows, accruals, share prices, and audit quality, as well as their interrelationships. In terms of sector, the boundaries of the study are the companies listed on ASE, which include the financial (banking and insurance), industrial, and service sectors. With respect to the geographic location, the boundary of this study is Jordan, which is an Asian, Middle East country. On the other hand, the temporal boundary of this study is the period 2002-2014, which is disintegrated into three intervals: six years before the economic crisis (2002-2007), the year of the economic crisis (2008), and six years after the economic crisis (2009-2014).